Pengaruh Konsumsi Susu Formula melalui Botol terhadap Kejadian Early Childhood Caries (ECC) Pada Anak Balita - Deli Mona (Faculty of Medicine, Universitas Andalas, 2023)
Objective: The purposeof this study is to determine the ef ect of formula milk through bottles onthei ncidence of Early Childhood Caries (ECC) in children under five. Methods: The methodsof this study was conducted by searching and reviewing various journals, literature reviews, and books on caries, Early Childhood Caries (ECC), formulamilk, the ef ect of formula milk. Result: Consumption of formula milk through a bottle canincrease the incidence of ECC. The increase in the incidence of ECCwasinfluenced by the duration, frequency, time and duration of consuming formulamilk. Conclusion: The conclusion is an ef ect of the consumption of formula milk throughbottles on the incidence of Early Childhood Caries (ECC) in children under fivewhich is influenced by the duration, frequency, time and duration of consuming formula milk.